A Picenian Warrior Who Lived in the Eight Century BC: A Hypothetical Reconstruction - Mauro Fiorentini (EXARC Journal)
The Iron Age in Central Italy is a period that begins in the tenth century BC and ends as the Romans take control over other Italic populations. Italy is divided longitudinally by the Apennines and the definition of ‘Central Italy’ includes the actual regions of Lazio and Toscana to the west, Umbria in the middle, Marche and Abruzzo on the east side of the Apennines. These regions border on Liguria and Emilia-Romagna in the north, Campania and Molise in the south. We also have the Tyrrhenian Sea on the shores of Lazio and Tuscany and the Adriatic Sea adjoining Marche and Abruzzo.